Coping with everyday stress and links to adaptation in diabetic adolescents with varying metabolic control - Seiffge-Krenke, Inge; Stemmler, Mark Kurt (Journal of Adolescent Health, 2003)
PURPOSE: To study coping with everyday stressors in a longitudinal sample of 98 adolescents with insulin-dependent mellitus (type 1) diabetes. METHODS: The adolescents with type 1 diabetes were classified into three homogeneous groups of metabolic control by latent class analysis, based on annual tests of hemoglobin A1 values. Questionnaires assessing frequent minor stressors as well as ways of coping with these stressors were given annually over the course of 4 years. Latent class analysis revealed three distinctive groups of metabolic control over time. Adolescents who exhibited continuously poor, satisfactory, and good metabolic control. Eighty percent of the adolescents stayed in the group assigned to them over the 4-year period. RESULTS: Adolescents with stable good metabolic control were characterized by lower levels of minor stressors that decreased over time, but those with stable satisfactory and poor metabolic control experienced continuously higher stress levels. Adolescents with stably good metabolic control also employed less avoidant coping in dealing with minor stressors, compared with the two other groups. CONCLUSIONS: Because of the danger of long-term complications, it is important to discriminate among different groups of metabolic control over time. Further, the impact of non-illness-related minor stressors on metabolic control should be considered for prevention purposes.
Keywords: Adolescents; Chronic illness; Coping; Diabetes mellitus; Latent class analysis; Longitudinal study; Metabolic control; Minor stressors; Germany